Response to hepatitis B vaccine in patients with non-hepatitis B chronic liver disease - Faruk AĞAN,; Yılmaz ÇOLAKOĞLU,; Atilla ÖKTEN,; Selim BADUR,; Levent ERDEM,; Selim GÜREL,; M. Derya ONUK,; Fatih BEŞIŞIK,; Sabahattin KAYMAKOĞLU, (Turkish Journal of Gastroenterology, 2019)
-